Exposure to continuous political violence: rational and experiential thinking styles, coping styles and post traumatic stress symptoms - Zvi, Liza; Cohen-Louck, Keren (Frontiers in Psychology, 2023)
Cognitive style is considered an important determinant of individual behavior. The aim of the present study was to examine the relations between rational and experiential thinking styles, coping styles and Post Traumatic Stress (PTS) symptoms among civilians exposed to continuous and ongoing exposure to political violence. Three-hundred and thirty-two Israeli adult citizens living in the south region of Israel reported on their experiences of exposure to political violence as well as level of PTS, coping styles, and preference toward rational and experiential processing style. Results showed that low rational thinking was related with elevated PTS, both directly and indirectly through the mediation of high emotion-focused coping. The findings suggest that rational thinking may serve as a protective factor against stress related to chronic exposure to political violence; conversely, a preference for low rationality may be a risk factor.